Effect of Cross-Linked Agents on the Morphology of Keratin/Egg White Blend Particles - Tanisood, S.; Srihanam, P. (Asian Journal of Chemistry, 2021)
The effect of cross-linked agents e.g. acetic acid, polyethylene glycol diglycidyl ether (PEGDE) and genipin on the morphology of keratin/egg white (KT/EW) blend particle formation by emulsification solvent diffusion method was observed. The concentration of blending solution and spinning rate (rpm) for obtaining desired particles were also studied. SEM images indicated that the shapes and sizes of KT/EW blend particles varied by the types of cross-linked agents and conditions used. A high concentration of acetic acid and PEGDE interrupted the rheology of blend solution, which interfered the particle formation as well as enhancing the protein denatured. In contrast, the high content of genipin did not affect the morphological shape and size of the particles. A high rotation per minute (rpm) rate was suitable for blend particle formation mixed acetic acid and PEGDE whilst suitable rpm rate for genipin was slower than 2 types of cross-linker. The morphological shape and surfaces of the KT/EW blend particles affected by the types and conditions used. These results obtained the informative data for the development of keratin/egg white blend particles to apply in specific fields such as drug-delivery system.